Diseño de un sistema de gestión y control operacional para una empresa que se dedica a la comercialización de repuestos de vehículos y servicios de reparación cuyas instalaciones se encuentran ubicadas en la ciudad de Guayaquil - Toala Robles, Hugo Fernando (2009)
At present the companies are not conscious of the care that they should have with each of the assets that form a part of the draft of the business and that with to happen from the time makes incur expenses that somehow might be avoided, for it that is necessary that each of these companies realize an analysis in such a way that they identify their more critical or so called sensitive assets to avoid later hurts as for corrective maintenance, this is obtained by a suitable planning of preventive maintenances, It is because of it that this is based on the development of a system of management and operational control, by what in the first part a conceptual frame is detailed of each one of the philosophies that there was studied for the implementation of the above mentioned system, as for example the props of the TPM, the analysis of way and effect of faults, the 5 "S", the OEE, the safety in the work and the good environmental practices, after this realize a due knowledge of the business, which consisted of the summary of certain historical information, taking the philosophies as a base already before mentioned, for what one shows records of maintenances, identification of the critical assets of the company, between others. In the third part is where one gives execution to the development of the system of management and operational control and is here where the whole necessary documentation appears inside the company accompanied of card of assets, counterfoil of analysis of way and effect of faults, counterfoil of evaluation of the risk between others. Already after realized this in the fourth part realizes basically a user's manual to use the developed system and finally the conclusions and recommendations to which come after the development of the system of management and operational control.